Screening Morocco : contemporary film in a changing society - Orlando, Valérie, 1963- (Research in international studies. Africa series, 2011)
Since 1999 and the death of King Hassan II, Morocco has experienced adramatic social transformation. Encouraged by the more openly democraticclimate fostered by young King Mohammed VI, filmmakers have begunto explore the sociocultural and political debates of their country whilealso seeking to document the untold stories of a dark past. Screening Morocco: Contemporary Film in a ChangingSociety focuses on Moroccan films produced and distributedfrom 1999 to the present. Moroccan cinema serves as an all-inclusive medium that providesa sounding board for a society that is remak.